INNOVASI KEBIJAKAN MUTU PENDIDIKAN UNTUK SEKOLAH RINTISAN: MENCIPTAKAN LINGKUNGAN BELAJAR YANG EFEKTIF - Mohammad Yasin Al Imron (Hijri, 2025)
This research aims to develop innovative policies to improve the quality of education in pilot schools, with a focus on creating an effective learning environment. The main objective of this study is to identify policies that support the quality of learning and analyze their impact on the effectiveness of the learning environment. The research method used is a qualitative approach with case study techniques, where data is collected through in-depth interviews, observation and document analysis at SMK NU Pesanggaran. The research results show that innovative policies involving active teacher involvement, adaptive curriculum, and appropriate use of educational technology have proven to play an important role in creating a conducive learning environment. Apart from that, support from school management in providing training to teaching staff and facilitating adequate learning resources also makes a significant contribution to improving the quality of education. In conclusion, innovative education quality policies can have a positive impact on pilot schools by creating more effective learning environments. This research recommendation includes implementing flexible and measurable policies to continue to improve the quality of learning in pilot schools